Structural features and antiviral activity of sulphated fucans from the brown seaweed Cystoseira indica - Mandal, Pinaki (2007)
Natural compounds offer interesting pharmacological perspectives for antiviral drug development. In this study, we have analysed sulphated-fucan-containing fractions isolated from the brown seaweed Cystoseira indica. The crude water extract (CiWE) and the main fraction (CiF3) obtained by anion exchange chromatography had potent antiviral activity against herpes simplex virus types 1 (HSV-1) and 2 (HSV-2) without cytotoxicity for Vero cell cultures. Furthermore, they had no direct inactivating effect on virions in a virucidal assay, and lacked anticoagulant activity. The mode of action of these compounds could be mainly ascribed to an inhibitory effect on virus adsorption. Chemical, chromatographic and spectroscopic methods showed that the major polysaccharide had an apparent molecular mass of 35 kDa and contained a backbone of α-(1→3)-linked fucopyranosyl residues substituted at C-2 with fucopyranosyl and xylopyranosyl residues. This sulphated fucan, considered the active principle of the C. indica water extract, also contained variously linked xylose and galactose units and glucuronic acid residues. Sulphate groups, if present, are located mostly at C-4 of (1→3)-linked fucopyranosyl units, and appeared to be very important for the anti-herpetic activity of this polymer.